2019
DOI: 10.3758/s13414-019-01804-6
|View full text |Cite
|
Sign up to set email alerts
|

The second number-estimation elbow: Are visual numbers greater than 20 evaluated differently?

Abstract: Numerosity perception has long been understood to be divided between subitizing and estimation. In a series of three experiments (total N = 113), a new number "elbow" point in the estimation of visual number for numerosities of about 20 dots is confirmed. Below 20, mean estimates are linear with a slope of about 1 and power-function exponents for numerosity estimation approximate unity, though estimate variance increases dramatically above about 6 elements. For numerosities above 20, estimates become increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 30 publications
3
33
1
Order By: Relevance
“…However, it is worth noting that for numerosities higher than those we used here (e.g., >20 items), a different visual mechanism for numerical quantification exploiting area and density information may be at play (Portley & Durgin, 2019). For example, it has been recently proposed that a dedicated system for density perception may operate over larger ranges (e.g., 100 items), in which items are highly cluttered or crowded, making their segmentation hard (Anobile et al, 2014, 2016; cf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is worth noting that for numerosities higher than those we used here (e.g., >20 items), a different visual mechanism for numerical quantification exploiting area and density information may be at play (Portley & Durgin, 2019). For example, it has been recently proposed that a dedicated system for density perception may operate over larger ranges (e.g., 100 items), in which items are highly cluttered or crowded, making their segmentation hard (Anobile et al, 2014, 2016; cf.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been recently proposed that a dedicated system for density perception may operate over larger ranges (e.g., 100 items), in which items are highly cluttered or crowded, making their segmentation hard (Anobile et al, 2014, 2016; cf. Portley et al, 2019). Specifically, these studies reported that the participants’ Weber fraction was constant over a low numerosity range, but, after a critical numerosity, it decreased proportionally to the square root of numbers (Anobile et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…System" in which estimated magnitudes scale logarithmically with number of tokens has been demonstrated for quantities in a second regime between 5 and ~50 (Atkinson et al, 1976;Feigenson et al, 2004;Piazza et al, 2007;Anobile et al, 2014). A third regime has been demonstrated that invokes texture-like processing with even larger quantities (Anobile et al, 2016;Portley and Durgin, 2019).…”
Section: Introductionmentioning
confidence: 95%
“…Dot coordinates and sizes were generated using a previously published algorithm (Piazza et al, 2004) that was designed to ensure that standard and oddball updates were statistically matched in terms of non-number properties. Dots were drawn with a dark inner dot surrounded by a brighter outer ring of equal area to eliminate confounding luminance and numerosity (Carlson et al, 1984;Huk and Durgin, 1996;Portley and Durgin, 2019). The inner dot and outer ring were made to have approximately the same number of pixels, but rounding error made a perfect luminance match with the background impossible.…”
Section: Stimulus Generationmentioning
confidence: 99%
“…In the absence of pretraining or other opportunities to calibrate spatial number estimation, Portley and Durgin (2019) observed that estimates of visual number were, on average, accurate up to about 20 items but underestimated actual number thereafter. By varying the range of numbers tested, Portley and Durgin showed that this effect was not due to some sort of central tendency but instead seemed to occur near 20 even when relatively few numbers beyond 20 were tested and most were below, or when relatively few numbers below 20 were tested and most were above 20.…”
Section: Introductionmentioning
confidence: 99%